Analysis of Indonesian Non-Oil and Gas Export Development by Manufacturing Sector 2016-2020 Period - Sri Endang Rahayu (AIBPM Publisher, 2021)
Indonesia's exports come from oil and gas and non-oil exports. Indonesia's non-oil and gas exports make a large contribution compared to exports from oil and gas. In terms of non-oil and gas exports by sector, the largest contribution to national exports is the export of the manufacturing. Indonesia's exports decreased in 2019 and 2020, respectively by 167,683 million US and 163,191.8 US. This is due to the Covid-19 pandemic that occurred in Indonesia and also hit many countries in the world. The purpose of this study is to analyze the development of non-oil and gas exports by manufacturing sector. The research approach is a quantitative description approach, where the data source is secondary data taken from BPS and satudata.kemendag.go.id. Indonesia's trade balance experienced a deficit in 2018 and 2019. In 2020 it experienced a surplus again after an improvement in economic conditions after a year hit by covid-19. The export development of the manufacturing decreased in 2017, 2018 and 2019. In 2020, it increased again by 2.91 percent. manufacturing exports contributed the largest to Indonesia's national exports until 2020, contributing 80.33 percent, of which manufacturing exports became Indonesia's mainstay export in the period before and during this Covid-19 period.